Influence of Thickness on Electrical and Optical Properties of Tellurium Thin Films Deposited by Chemical Spray Pyrolysis - Janan SAADİE (International Journal of Applied Methods in Electronics and Computers, 2015)
In this paper, Spray pyrolysis was applied to deposit Tellurium thin film on glass substrates at 498 ± 283 K in order to investigate the influence of thickness on the electrical and optical properties of the prepared thin films. The film thicknesses were measured in situ by weighting method. The thicknesses were from (150 to 800) nm. X-ray diffraction results showed that the Te thin films formed were polycrystalline with hexagonal structure. The effect of film thickness on the electrical properties of the films was investigated by Hall Effect measurement through the analysis of the I-V plots. The conductivity of the films and carrier concentration were highly increased when the films became thicker. Transmission and absorption spectrum of the prepared thin film had been recorded using UV-VIS-NIR spectrophotometer in the photon wavelength range of 300 - 2000 nm. The values of some important optical parameters of the studied films (absorption coefficient, and optical band gap energy) were determined using these spectra. The transmittance showed better results when thicknesses were being increased. In addition, the absorption coefficient is higher for thinner films and decreases for thicker films showing little dependence for absorption coefficient on thin film thickness in infra-red region of the wavelength. It was found from the optical properties studies that the type of transition of Te film is direct transition. Also, the optical energy band gap was evaluated for different thicknesses. The results have shown that the optical energy band gap was increased by the increase of thickness. Experiments and measurement results are presented.